Institutional analysis of water governance in the Colorado River Basin, 1922–2022 - Lawless, Krista L.; Garcia, Margaret; White, Dave D. (Frontiers in Water, 2024)
The 1922 Colorado River Compact started the long history of water governance in the Colorado River Basin. Over the last century, the institutional structure has shaped water governance in the basin. However, an understanding of the long-term evolution is lacking. This study examines how water management strategies have evolved at the basin scale by incorporating institutional, temporal, and network structure analysis methods to examine long-term changes. Content analysis was employed to systematically investigate encouraged and/or discouraged water management actions at different rule levels. The water governance network was examined at four points in time to map the institutional structure, actors, and governance level at which rules are issued and targeted. Using institutional analysis, we found constitutional, operational, and collective-choice level rules for water supply, storage, movement, and use have been altered via layering of new governance rules without major rule or responsibility alteration. The network analysis results indicate that key decision-making positions have remained and actors who issue and are targeted by the rules lack significant change. We found original positions of power have been maintained, potentially stagnating the space for problem-solving and management strategy renegotiation. Our results indicate that path dependency has shaped water governance and who is able to influence decision-making.